Am I Supposed to Create Knowledge?: Pedagogical Challenges of Doctoral Mentors - Jung-ah Choi (Educational Process: International Journal)
This paper discusses the nature and characteristics of doctoral dissertation learning and the role of mentor in the dissertation stage. Doctoral level education requires a considerable degree of learner’s independent thinking. While independence has been discussed as a personal trait or in relation to the socialization of doctoral education, independence has rarely been discussed as a higher level of cognitive development necessary to create new knowledge. When students transition from a consumer of knowledge to a creator/owner of knowledge, they are required to adopt a new epistemology, i.e., a new way of knowing. How do doctoral advisors/mentors successfully open students to a new way of knowing? This paper addresses the pedagogical foundations of doctoral advising. Drawing on theories of student-centered pedagogy and self-directed learning, this paper attempts to conceptualize the doctoral supervisor’s role in the case of doctoral supervision.